Capacidad de autocuidado del adulto mayor, hospitalizado en los servicios de medicina y cirugía del Hospital Herminda Martín de Chillán, Chile - Gloria Araneda Pagliotti; Ximena Isla Lund; Marta Jiménez Orellana (Universidad de Alicante, 2012)
This study describer the capacities and the sociodemographic and health factors that influence those capacities of people over 60 years of age. The Barthel Scale (1965), the Pfeiffer Questionnaire (1975) and the Analogous Visual Scale for Pain were applied to 196 hospital patients. Results show that the 80.1% of the sample group are independent in their self-care ability, 15.8% were fairly independent and only 4.1% were dependent. Most of the subjects are between 60 and 70 years old they live in urban areas have attended elementary school. They are illiterate, and have a couple. 76% of the 61.2%, coming from the urban area, are independent. The literacy leved showed direct relation to self-care capacity and an indirected relation with the number of times they get into the hospital. Over 6.1% and 7.1% need total or partial assistance for intestinal or vesical elimination, respectively and 11.3%, for feeding themselves. Almost 20% of all of them have a certain degree of dependence for their morning care. In relation to their knowledgements on health: most of them 85% know little or nothing about their illness, half of them know the effects or medicines and the schedule for their administration, more than half of them have no idea of their blood preasure. In general, results showed but mental health, swallowing difficulties and the knowledge about the medicines they take, show a significant statistical relation to their self-care capacity.